Modern Marriage and the Lyric Sequence - Hedley, Jane (Springer International Publishing, 2018)
Modern Marriage and the Lyric Sequence investigates the ways in which some of our best poets writing in English have used poetic sequences to capture the lived experience of marriage. Beginning in 1862 with George Meredith's Modern Love, Jane Hedley's study utilizes the rubrics of temporality, dialogue, and triangulation to bring a deeply rooted and vitally interesting poetic genre into focus. Its twentieth- and twenty-first-century practitioners have included Edna St. Vincent Millay, Robert Lowell, Rita Dove, Eavan Boland, Louise Glück, Anne Carson, Ted Hughes, Claudia Emerson, Rachel Zucker, and Sharon Olds. In their poetic sequences the flourishing or failure of a particular marriage is always at stake, but as that relationship plays out over time, each sequence also speaks to larger questions: why we marry, what a marriage is, what our collective stake is in other people's marriages. In the book's final chapter gay marriage presents a fresh testing ground for these questions, in light of the US Supreme Court's affirmation of same-sex marriage.